Reduced Heart Rate Variability as A Risk Factor for Cardiovascular Disease in Young Healthy Adults with Low and High Body Mass Indexes – A Descriptive Study - Niveatha S; Raju, Aruna; Latha R; Tamilselvan K; Priyadharshini U, Karthika; AK, Jayamala; Lydia Shadrack, Graceline Margarat (National Journal of Community Medicine, 2022)
Background: Heart rate variability (HRV) is a used to assess autonomic nervous system input to the heart. Studies on the impact of HRV on underweight are limited. Aims/Objectives: To evaluate HRV in age matched young adults of different BMI category. Methodology: This cross-sectional study was done among healthy young adult volunteers between 18 and 25 years of age. Anthropometric variables were measured. ECG was recorded in lead II configuration for 5 minutes. Heart rate variability was analysed with Kubios HRV analyzer. Results: HRV indices were reduced in underweight (UW), overweight (OW) and obese group compared to normal weight (NW) BMI group. Second order polynomial regression between BMI and HF log power in both genders shows an inverted U-shaped relationship with BMI. The association between BMI, waist circumference and body fat (percentage) with HRV indices shows a significant relation to heart rate variability among which waist circumference (WC) shows a greater association with HRV indices than BMI. Comparison of HRV parameters among men and women of different BMI group shows female had greater heart rate variability compared to males across BMI Conclusions: underweight individual also have increased cardiovascular risk like obese group and abdominal obesity is better indicator of cardiovascular risk than BMI.